2000
DOI: 10.1111/1469-7610.00600
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Peer Relationship Problems and Later Risks of Educational Under‐achievement and Unemployment

Abstract: This paper examines relations between the extent of children's peer relationship problems at age 9 and their later risks of educational under-achievement and unemployment by the age of 18 years. Results showed that children with high rates of early peer relationship problems were at increased risk of under-achievement and unemployment when compared with children with low rates of early peer relationship problems. These elevated educational and occupational risks were explained by two processes. First, associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…These components are not independent. Where there are declines in emotional well-being, there are also declines in peer relationship quality, and academic performance, though causality has yet to be established (e.g., Woodward and Fergusson, 2000; Reijntjes et al, 2010; Mundy et al, 2017; Rahman et al, 2018). Although many students adapt with relatively few issues, others find the transition impacts one, two, or all of these domains.…”
Section: Introductionmentioning
confidence: 99%
“…These components are not independent. Where there are declines in emotional well-being, there are also declines in peer relationship quality, and academic performance, though causality has yet to be established (e.g., Woodward and Fergusson, 2000; Reijntjes et al, 2010; Mundy et al, 2017; Rahman et al, 2018). Although many students adapt with relatively few issues, others find the transition impacts one, two, or all of these domains.…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have explored peer stigma in childhood and adolescence, the research that exists shows that peer stigmatisation is a widespread problem (Walker, Coleman, Lee, Squire, & Friesen, 2008). Research shows that rejected children with emotional and behavioural problems are at risk of experiencing adverse developmental outcomes from educational underachievement and unemployment (Woodward & Fergusson, 2000) to delinquency and problem behaviour (Ladd & Burgess, 2001;Wentzel, 2003), even after controlling for other risk factors and baseline levels of externalising behaviour. As mental health problems persist over time (Kim-Cohen et al, 2003), people are susceptible to potential lifelong stigmatisation, which may have originated in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…These skills are important given that studies of the general population show that poor social competence is associated with educational underachievement, peer rejection, internalizing problems, and school disengagement during adolescence as well as poorer social, occupational, and family functioning in adulthood. [7][8][9][10][11] Currently, a small but growing body of studies suggests that children born VPT are subject to a range of social and behavioral difficulties that may affect their life-course opportunities. [12][13][14] Several contemporary follow-up studies have also found an increased risk of autism spectrum disor-ders and related behaviors in survivors of VPT birth.…”
mentioning
confidence: 99%